அச்சுறுத்தும் பாலை நிலம் / Dreadful Palai Land - மா.ரேவதி / M. Revathi; முனைவர் அ. கோவிந்தராஜன்/Dr. A. Govindarajan (Chenkaantal)
This article is based on the Dreadful Palai Land which has a desert-like structure of ancient Tamil Nadu. It examines the ideas of the Palai land mentioned by Tolkappiyar and the opinions of other Tamil authors. The views of the commentators and the views of Sangam authors are also examined that Palai land will be formed by combining Kurinji and Mullai when it had been destroyed. From ancient Tamil Nadu to today's Tamil Nadu, there was no permanent land called Palai land. It is also known that fertile land areas are changing their nature and turning into deserts due to the scorching Sun, water crisis and other ecocritical issues. Palai songs can be used to describe the extent to which the desert has become a land of terror due to the lack of basic needs. It is known that wayfarers are threatened by animals and subjected to persecution like killing and robbery by the bandits of the area. Such ideas can be found in Palai Thani songs. Hence, this article elicits the facts of Palai Land from authentic sources.